2020
DOI: 10.1002/pc.25690
|View full text |Cite
|
Sign up to set email alerts
|

Novel waterborne poly(urethane‐urea)/silica nanocomposites

Abstract: A series of novel transparent mechanically strong waterborne poly(urethaneurea)/silica nanocomposites were prepared by mixing a waterborne poly(urethane-urea) dispersion with aqueous nanosilica, followed by slow water evaporation. This procedure is simple, environmentally friendly and energetically undemanding. The silica content in the nanocomposite film varied from 0 to 50 wt%. Based on changes of tensile characteristics, for example, Young's modulus values, three types of behavior were observed: typical ela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…In order to allow an adequate dispersion into the PUD, the nanosilica particles in the aqueous dispersion should be separated and the most literature [ 30 , 31 , 32 , 41 ] have proposed severe mechanical stirring. However, in this study, a mild mechanical stirring of the aqueous nanosilica dispersion and the PUD was used, combined with the addition of small amounts (0.1–0.5 wt.%) of nanosilica.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In order to allow an adequate dispersion into the PUD, the nanosilica particles in the aqueous dispersion should be separated and the most literature [ 30 , 31 , 32 , 41 ] have proposed severe mechanical stirring. However, in this study, a mild mechanical stirring of the aqueous nanosilica dispersion and the PUD was used, combined with the addition of small amounts (0.1–0.5 wt.%) of nanosilica.…”
Section: Resultsmentioning
confidence: 99%
“…The influence of the addition of the nanosilica dispersion to the waterborne polyurethane on its adhesion properties is not clear in the existing literature. Both increased adhesion [ 29 , 31 , 33 ] and decreased adhesion to different substrates [ 21 ] of silica–waterborne polyurethanes have been shown, the increased adhesion was related to the existence of interactions between the nanosilica and the polyurethane, and to the extent of the nanosilica agglomeration.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the commonly used inorganic fillers, SiO 2 nanoparticles have the advantages of small particle size, large specific surface area, high hardness, low refractive index, and commercial availability 29–31 . SiO 2 nanoparticles can improve PU's mechanical properties, thermal stability, shape memory behavior, and gas permeability 32–34 . Many studies have shown that the silanol (Si‐OH) groups on the SiO 2 surface affect the microphase separation of PU/SiO 2 composites because these groups may interact with HSs or SSs of PU matrix 10,13,29,31,35 …”
Section: Effect Of Filler Typementioning
confidence: 99%